Elements Influencing the Caliber of Electronic Logistics Services in Vietnam - Tan, Trinh Le; Tran, Tung Minh (Journal of Applied Data Sciences, 2024)
This study investigated the factors influencing the quality of electronic logistics (E-logistics) services in Da Nang, Vietnam, aiming to assist service providers in improving their operations. The purpose of the study was to identify key determinants of E-logistics service quality to provide actionable insights for service enhancement. The research utilized both qualitative and quantitative methods, starting with qualitative research involving interviews with 20 managers to refine the scale and survey questions tailored to the Vietnamese context. Subsequently, quantitative analysis was conducted using data from 196 respondents, evaluated through linear regression models. The findings revealed six key factors significantly impacting E-logistics service quality in Da Nang: customer perception, technology and security, legal infrastructure, intellectual property and consumer protection, electronic payment systems, and human resources. Together, these factors explained 80% of the variance in E-logistics service quality. Among these, human resources (β=0.464, p0.001) and customer perception (β=0.226, p0.001) were found to be the most influential, followed by technology and security (β=0.143, p0.05), electronic payment systems (β=0.125, p0.05), legal infrastructure (β=- 0.016, p0.05), and intellectual property and consumer protection (β=0.046, p0.05). The reliability of the measurement scales was high, with Cronbach's alphas ranging from 0.832 to 0.857. The novelty of this research lies in its comprehensive analysis of E-logistics service quality within the context of an emerging market, providing valuable insights for both academic and practical applications. The results underscore the importance of businesses adapting their strategies in response to digital transformation to enhance service quality and meet evolving customer expectations. Future research should focus on longitudinal studies to assess the impact of these factors over time and explore additional variables that may influence E-logistics service quality in different regional contexts.